2008
DOI: 10.1097/shk.0b013e3180cab3ce
|View full text |Cite
|
Sign up to set email alerts
|

Gut Luminal Lactate Measured by Microdialysis Mirrors Permeability of the Intestinal Mucosa After Ischemia

Abstract: The aim of the present study was to investigate the influence of a prolonged initial intestinal ischemic insult on transmucosal permeability after a subsequent ischemic event and whether microdialysis of biomarkers released to the gut lumen is able to reflect changes in intestinal permeability. The superior mesenteric artery was cross-clamped for 60 min followed by 4 h of reperfusion in 16 pigs. Nine pigs had a second cross-clamp of 60 min and 3 h of reperfusion, whereas seven pigs were observed for a further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
2
24
0
3
Order By: Relevance
“…Several techniques are available to study the microcirculation of the intestine. Deteriorations of the intestinal microcirculation can be assessed indirectly by analyzing tissue oxygenation with Clark electrodes or by monitoring intramucosal pH (pHi) and pCO 2 (PiCO 2 ) using tonometry [17][18][19][20]. In addition, tissue reflectance spectrophotometry may give information on microvascular hemoglobin oxygen saturation (HbO 2 ) and Laser Doppler velocimetry can assess relative changes of microvascular blood perfusion [21,22].…”
Section: Techniques For the Study Of Intestinal Microcirculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques are available to study the microcirculation of the intestine. Deteriorations of the intestinal microcirculation can be assessed indirectly by analyzing tissue oxygenation with Clark electrodes or by monitoring intramucosal pH (pHi) and pCO 2 (PiCO 2 ) using tonometry [17][18][19][20]. In addition, tissue reflectance spectrophotometry may give information on microvascular hemoglobin oxygen saturation (HbO 2 ) and Laser Doppler velocimetry can assess relative changes of microvascular blood perfusion [21,22].…”
Section: Techniques For the Study Of Intestinal Microcirculationmentioning
confidence: 99%
“…Langenbecks Arch Surg (2011) 396:[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] …”
unclassified
“…Animal studies and clinical observations revealed that ischemia leads to increased permeability of the intestinal epithelial barrier, resulting in translocation of pathogenic bacteria and endotox- ins (12)(13)(14). As a consequence, inflammation, sepsis and multiorgan failure may develop, leading to life-threatening conditions (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose levels are reduced inside the mesenteric vessels, intraluminally, but also intraperitoneally. 13 During this study, the L/P ratio remained at high levels for the first 3 days of hospitalization. In fact, an L/P ratio of 25.94 is recommended as a baseline value, over which the survival rate is significantly decreased, as clearly observed in this study.…”
Section: Discussionmentioning
confidence: 96%